Criminal Investigation Stages Based on "Visum Et Repertum" as Evidence of Rape in Bone Regency - Rika Damayanti; Nurmi Sari; Gustika Sandra (Journal of Public Representative and Society Provision, 2026)
The crime of rape is an act that is considered contrary to all existing norms, because it is done by forcing someone (a woman) to have sex outside of marriage. The purpose of this study is to determine the function of the post-mortem examination (visum et repertum) at the investigation stage in uncovering a crime of rape. And to determine the efforts taken by investigators if the results of the post-mortem examination do not contain information about signs of violence on the rape victim, in order to obtain the material truth of a rape case. The research method uses a sociological juridical approach. This approach departs from statutory regulations that are oriented towards studies that lead to the fulfillment of evidence in conducting investigations. The sample in this study was the Head of the Criminal Investigation Unit of the Bone Police and 2 police officers in the Criminal Investigation Unit of the Bone Police. The results of this study showed that the results contained in the post-mortem examination can be initial evidence for investigators to take other actions in uncovering a case of rape. Suggestions should be that investigators can consider in reading and applying the results of the post-mortem examination, especially knowledge for investigators regarding things that might affect the results of the post-mortem examination. This knowledge is important so that investigators do not interpret the results of the post-mortem examination obtained carelessly, which can then influence and determine the investigator's follow-up actions in examining the case.